Nitrogen-doped graphene/carbon nanohorns composite as a high-performance supercapacitor electrode. Issue 11 (November 2017) - Lin, Xiao-Qiang; Wang, Wen-Dong; Lü, Qiu-Feng; Jin, Yan-Qiao; Lin, Qilang; Liu, Rui
Abstract: Nitrogen-doped graphene/carbon nanohorns composite (NGLC) was prepared by one-step co-pyrolysis of graphene oxide, carbon nanohorns (CNHs), urea, and lignosulfonate. CNHs as spacers were inserted into graphene nanosheets. The introduction of CNHs and the loosened nano-structure of NGLC make it achieve a high specific capacitance of 363 F g −1 at a discharge current density of 1 A g −1, and NGLC exhibits an ultrahigh stability of 93.5% capacitance retention ratio after 5000 cycles. The outstanding comprehensive electrochemical performance of NGLC could meet the need of the future acted as an efficient supercapacitor electrode material.